Light‐Activated Tissue‐Integrating Sutures as Surgical Nanodevices. Issue 14 (8th May 2019) - Ghosh, Deepanjan; Urie, Russell; Chang, Andy; Nitiyanandan, Rajeshwar; Lee, Jung Keun; Kilbourne, Jacquelyn; Rege, Kaushal
Abstract: Sutures are typically the primary means of soft tissue repair in surgery and trauma. Despite their widespread use, sutures do not result in immediate sealing of approximated tissues, which can result in bacterial infection and leakage. Nonabsorbable sutures and staples can be traumatic to tissue, and the trauma can be exacerbated by their subsequent removal. Use of cyanoacrylate glues is limited because of their brittleness and toxicity. In this work, laser‐activated tissue‐integrating sutures (LATIS) are described as novel nanodevices for soft tissue approximation and repair. Incorporation of gold nanorods within fibers generated from collagen result in LATIS fibers which demonstrate robust photothermal responses following irradiation with near infrared laser light. Compared to conventional sutures, LATIS fibers result in greater biomechanical recovery of incised skin in a mouse model of skin closure after spine surgeries. Histopathology analyses show improved repair of the epidermal gap in skin, which indicate faster tissue recovery using LATIS. The studies indicate that LATIS‐facilitated approximation of skin in live mice synergizes the benefits of conventional suturing and laser‐activated tissue integration, resulting in new approaches for faster sealing, tissue repair, and healing. Abstract : The generation and characterization of laser‐activated tissue‐integrating sutures (LATIS) are described as a novel nanodevice for soft tissue approximation and repair. LATIS facilitates soft tissue approximation by synergizing the benefits of conventional suturing and laser‐activated tissue integration. LATIS results in greater biomechanical recovery and improved healing of murine skin in vivo without any severe inflammatory responses compared to commercial sutures.